PH-dependent inhibition of AHL-mediated quorum sensing by cell-free supernatant of lactic acid bacteria in Pseudomonas aeruginosa PAO1. (May 2020) - Rana, Shikha; Bhawal, Shalaka; Kumari, Ankita; Kapila, Suman; Kapila, Rajeev
Abstract: Antibiotic mediated therapies target the growth-related processes of the pathogen hence imparting a strong selection pressure on the pathogen to develop antibiotic resistance. Recently anti-virulence strategies have gained lots of attention amongst the scientific community, wherein instead of inhibiting the normal growth of pathogens, it interferes with the regulation of virulence factors of the pathogens and impede their pathogenesis. In Pseudomonas aeruginosa, the virulence mechanism accountable for various types of infections in humans depends on N-acyl homoserine lactone (AHL) mediated quorum sensing. So quenching of these molecules, pose as a promising tool against P. aeruginosa pathogenesis. Lactic acid bacteria cell-free supernatant (acidic and neutralized) were evaluated in quorum quenching of P. aeruginosa PAO1 (MTCC 3541) after their initial screening for anti-biofilm potential against this pathogen.Though the reduction in biofilm formation with acidic and neutralized supernatants of lactic acid bacteria revealed strain specific response but acidic fractions showed much stronger (P ≤ 0.05) inhibition of biofilm irrespective of the type of challenge given to P. aeruginosa with lactic acid bacteria. The acidic fraction of supernatants ( L. lactis, L. rhamnosus and L. fermentum ) not only showed a significant reduction (P ≤ 0.05) in auto-inducer AHL levels but also diminished elastase activity which was among important virulence characters directly controlled by the quorum sensing signaling. Moreover, significant decrease (P ≤ 0.05) in mRNA expression of lasI and rhlI in presence of acidic fractions of lactic acid bacterial supernatants further confirmed the quorum quenching process in P. aeruginosa . Highlights: Lactic acid bacteria reduced the biofilm formation of Pseudomonas aeruginosa . Acidic cell free extract appeared more potent in quorum quenching. Lactic acid bacteria modulated the expression of virulence factors of P. aeruginosa .